Annotated checklist and distribution of the Socotran Archipelago Herpetofauna (Reptilia) - Razzetti, Edoardo; Sindaco, Roberto; Grieco, Cristina; Pella, Francesca; Ziliani, Ugo; Pupin, Fabio; Riservato, Elisa; Pellitteri-Rosa, Daniele; Butikofer, Luca; Suleiman, Ahmed Saeed; Al-Aseily, Badar Awadh; Carugati, Caterina; et al. (Zootaxa, 2011)
We update the knowledge on the 30 terrestrial reptile species of Socotra, an archipelago well known for its highly endemic flora and fauna. We use the records obtained during several surveys throughout all the islands of the archipelago, carried out between 2007 and 2010, as well as the bibliographic records. We recorded all the known species of terrestrial reptiles for the islands (Chamaeleo monachus, Haemodracon riebeckii, Haemodracon trachyrhinus, Hemidactylus dracaenacolus, H. granti, H. homoeolepis, H. flaviviridis, H. forbesi, H. inintellectus, H. oxyrhinus, H. robustus, H. pumilio, Pristurus abdelkuri, P. guichardi, P. obsti, P. insignoides, P. insignis, P. sokotranus, P. samhaensis, Mesalina balfouri, M. kuri, Hakaria simonyi, Trachylepis socotrana, Pachycalamus brevis, Leptotyphlops filiformis, L. macrurus, L. wilsoni, Typhlops socotranus, Ditypophis vivax, Hemerophis socotrae). We report for the first time the occurrence of Hemidactylus robustus in Samha Island. H. homoeolepis is excluded from the fauna of Abd al-Kuri Island.